Psychologists’ experiences with telepsychology during the COVID-19 pandemic in South Africa - Anne S. Raju; Helene E. le Roux; Paul J. Pretorius; Omololu Aluko (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2024)
Background: During the COVID-19 pandemic, South African psychologists started to use telepsychology to continue providing services. However, diverse factors may influence psychologists’ decisions regarding the use of telepsychology.